Formação de professores, saberes, reflexividade e apropriação da cultura digital no Projeto Um Computador por Aluno (UCA) - Burlamaqui, Akynara Aglae Rodrigues Santos da Silva (2014)
This study investigates teacher training and cognitive practice of teachers in a Basic Education school that adopted the Project One Computer per Student (OCS) in their school routine. Its relevance consists in provide directions for the continuation of training activities on the Project and guide the teachers with their pedagogical practices using the laptop model one to one. The thesis defended is that the educator formation for social using of digital media (specially the laptops from the Project UCA) gives space to establish new sociotechnical relationships, of new social and professionals practices, new identitary components and a process of reflexivity and knowledge reconstruction to teach. We reaffirm the importance of reflexivity and appropriation of digital culture for the better development of teaching practice using the Information and Communication Technologies (ICTs), giving focus to the aspects of social and professional use of the technology. The study is part of the qualitative aspect and is a procedural tracking based on principles of ethnographic research. As procedures and methodological tools, were used: intensive observation of school environments, documental analysis, focal group, semi-structured questionnaires and semi-structured individual interviews. The research was held in a public school in the city of Parnamirim - RN. The subject sample relates to 17 teachers, coming from the elementary school I and II, Youth and Adult Education and High School, who went through the process of training UCA and having entered the laptops in their teaching. The research corpus is structured based on the messages built into the process of data collection and is analyzed based on principles of Content Analysis, specified by Laurence Bardin (2011). Was taken as theoretical reference studies by Tardif (2000; 2011), Pimenta (2009), Gorz (2004, 2005), Giddens (1991), Dewey, J. (1916), Boudieu (1994; 1999), Freire (1996; 2005), among others. The analysis indicates a process of reconstruction / revision of knowledge to teach and work in digital culture, being these knowledges guided by the experience of the subjects investigated. The reconstructed knowledges will be revealed from a categorization process. The following groups of knowledges: "technical knowledges", "didactic-methodological knowledges and knowledges of professionalization" were built on the assumption of ownership of digital culture in the educational context. The analysis confirms the appearance of new ways of sociability when acquiring other forms of acting and thinking ICTs, despite the environment adverse to the reflexivity shared among the teachers. Also reveals, based on the ownership concept present on the data analysis, the construction of meanings of belonging and transformation of individuals into social routes from the interweaving of the teaching practice with the digital culture. Emphasizes, finally, the importance of a training for use of ICTs that exceeds the instrumentation, in other words, what we call "technical knowledges", but taking on its structural basis the shared reflection, the opening for the ressignificance (new meaning) and reconstruction of new knowledges and practices and that really allows, to the teacher, the living of an experience capable of providing socio-technical transformations of their relationships